Eliminating the left-brain/right-brain conflict present in the traditional Critical Path Method. (2nd October 2007) - Paxton, John
In presenting Critical Path Method in the traditional manner, students experience a left-brain/right-brain conflict as they switch back and forth between the network diagram and the table ultimately used to calculate the slack values. For some students, this is not a problem; however, for many students, this is confusing to the point that these students refuse to use one or the other of these two essential tools. I have devised a presentation scheme that eliminates this conflict while simultaneously retaining all of the information content. This paper presents this scheme along with empirical evidence of its efficacy.